2005
DOI: 10.1111/j.1399-6576.2005.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative caudal block prevents emergence agitation in children following sevoflurane anesthesia

Abstract: Our results show that in children undergoing inguinal hernia repair, pain control with a preoperative caudal block as compared to intraoperative intravenous fentanyl significantly reduces the incidence of emergence agitation and pain scores following sevoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 22 publications
0
55
0
2
Order By: Relevance
“…It is widely believed that reducing or eliminating pain decreases the incidence of emergence agitation after sevoflurane anesthesia. Several studies demonstrated that regional block, opioids, and nonsteroidal antiinflamatory drugs decrease the incidence of emergence agitation [10,11,[13][14][15]. However, emergence agitation often occurs even after adequate pain treatment or after procedures that are not associated with pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that reducing or eliminating pain decreases the incidence of emergence agitation after sevoflurane anesthesia. Several studies demonstrated that regional block, opioids, and nonsteroidal antiinflamatory drugs decrease the incidence of emergence agitation [10,11,[13][14][15]. However, emergence agitation often occurs even after adequate pain treatment or after procedures that are not associated with pain.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to exclude the influence of post-operative pain on EA and decrease the incidence of EA. Due to regional block, opioids and nonsteroidal anti-inflammatory agents have been reported to decrease the incidence of EA (35,36). However, EA still occurs, even after adequate pain treatment or procedures that are not associated with pain (37).…”
Section: Group ------------------------------------------------------mentioning
confidence: 99%
“…Pre-school aged children, preoperative anxiety, inadequate pain control, type of the surgery (especially ophthalmological and otorhinolaryngological), anesthesia method are defined as the risk factors for EA in children. [3][4][5][6][7] Sevoflurane and desflurane are the preferred inhalational anesthetic agents for the induction of anesthesia in children. However, these agents have been reported to increase the ratio of EA because of their low blood/gas partition coefficients.…”
Section: Letter To the Editormentioning
confidence: 99%